2013
DOI: 10.1002/eji.201343388
|View full text |Cite
|
Sign up to set email alerts
|

NKp46 regulates allergic responses

Abstract: Natural killer (NK) cells are cytotoxic cells that are able to rapidly kill viruses, tumor cells, parasites, bacteria, and even cells considered “self”. The activity of NK cells is controlled by a fine balance of inhibitory and activating signals mediated by a complex set of different receptors. However, the function of NK cells is not restricted only to the killing of target cells, NK cells also possess other properties such as the secretion of proangiogenic factors during pregnancy. Here, we demonstrate anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
(79 reference statements)
0
26
2
Order By: Relevance
“…Again, the absence of NKp46 + cells did not significantly influence cardinal features of HDM‐driven asthma (Fig C–E), although there was a trend toward lower HDM‐specific IgG1 serum levels in NKp46‐DTA mice. These findings contrast with earlier studies in OVA/alum‐based allergic asthma models (Korsgren et al , ; Ple et al , ; Ghadially et al , ). To exclude allergen‐dependency, littermate and NKp46‐DTA mice were subjected to an OVA/alum‐based allergic asthma model (Fig F and G).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Again, the absence of NKp46 + cells did not significantly influence cardinal features of HDM‐driven asthma (Fig C–E), although there was a trend toward lower HDM‐specific IgG1 serum levels in NKp46‐DTA mice. These findings contrast with earlier studies in OVA/alum‐based allergic asthma models (Korsgren et al , ; Ple et al , ; Ghadially et al , ). To exclude allergen‐dependency, littermate and NKp46‐DTA mice were subjected to an OVA/alum‐based allergic asthma model (Fig F and G).…”
Section: Resultscontrasting
confidence: 99%
“…Initial studies have used NK1.1 or asialo-GM1 (ASGM1) depleting antibodies (Korsgren et al, 1999;Ple et al, 2010), or mice genetically deficient for the activating receptor NKp46 (Ghadially et al, 2013) or NKG2D (Farhadi et al, 2014). These studies showed that NK cells were crucial and non-redundant for asthma development induced by ovalbumin (OVA)/alum (Korsgren et al, 1999;Ple et al, 2010;Ghadially et al, 2013) or chronic HDM exposure (Farhadi et al, 2014). In contrast, increased pulmonary NK cell numbers were recently correlated with reduced HDM-mediated airway inflammation in mice (Ferrini et al, 2016;Simons et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study examined the relation between the expression of NCR and cytokines production for decidual NK cells, reporting that NKp46 + decidual NK cells did not have function for cytokine secretion, but that NKp44 + and NKp30 + decidual NK cells did. However, other researchers have reported a relation between low NKp46 expression and decreased production of cytokines, such as IFN‐γ and IL‐13 in allergic responses . Previously, we have also reported the relation between the expression of NKp46 on NK cells and cytokines production by NK cell .…”
Section: Discussionmentioning
confidence: 48%
“…They were shown to participate in many immunological and regulatory processes including viral 111 , bacterial and fungal infections 1214 , cancer 8,9,1520 , graft versus host disease 21 , autoimmunity 2224 , allergy 25 and pregnancy 26 . NK cells kill their targets when signals from activating and co-activating receptors overcome inhibitory signals 27 .…”
Section: Introductionmentioning
confidence: 99%